Written Feedback: Exploring the Reflections of Upper Primary Music Students at Two Western Australian Schools - Goh, Kimberley Puay Theng (Curtin University, 2019)
This qualitative practitioner research study investigated the reflections and responses of upper primary music students in relation to written teacher feedback. Findings from this study provided insights into students’ perspectives on written feedback, personal responses to written feedback, and processing of written feedback. A key outcome of this study was the development of practical recommendations to assist teachers in empowering primary school students to use written feedback more effectively.